Association of fat mass and obesity associate (FTO) single nucleotide polymorphisms in the first intron and obesity risk among Indonesians - Benedikta Diah Saraswati; Luluk Yunaini; Dwi Anita Suryandari (Published by Universitas Gadjah Mada, 2024)
Obesity is one of the global pandemics characterized by an excessive fat buildup due to disruption of energy homeostasis in the body. As obesity is a risk factor for many other non-communicable diseases such as diabetes and coronary heart disease, it is crucial to understand the risk factors that contribute to the pathogenesis of obesity. Although obesity is mainly caused due to unhealthy lifestyles, genetic predisposition also plays a part in the pathogenesis of obesity. Individuals who carry risk alleles for genes that control energy balance in the body have a greater risk of developing obesity. Fat mass and obesity associate (FTO) is a gene strongly correlated with obesity and is widely expressed in the hypothalamus. This gene is predicted to have 89 common variations that affect obesity-related phenotypes. Among Indonesians, the three most studied single nucleotide polymorphisms (SNPs) in the first intron of the FTO gene are rs1421085, rs17817449, and rs9939609. They are strongly associated with obesity’s related traits such as weight gain, fat mass, body mass index (BMI), waist, and hip sizes. rs993609 is the most studied among diverse ethnicities in Indonesia, with AA genotype and allele A as a risk allele.